2012
DOI: 10.1055/s-0032-1326932
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Percutaneous Nephrostomy for the Diagnosis and Management of Pyonephrosis

Abstract: Emergent percutaneous nephrostomy is a potentially lifesaving procedure with a high technical success rate, minimal morbidity, and long safety record that is often used in the setting of an obstructed and infected renal collecting system (i.e., pyonephrosis). This article discusses all aspects of the emergent placement of nephrostomy catheters including indications, techniques, results, and complications. Differences between emergent and nonemergent placement of percutaneous nephrostomy catheters are also addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Yuruk et al [ 32 ] showed that the CT values of pus in pyonephrosis patients were significantly higher than those of patients with hydronephrosis; the difference was statistically significant. Because pus often contains infectious substances, cell debris, and large numbers of micro-organisms, the CT value of the pus is higher than hydronephrosis, and application of CT values based on CT thin-layer scanning to identify hydronephrosis and pyonephrosis yields satisfactory results [ 33 ]. In clinical practice, a significant increase in CT attenuation value of hydronephrosis should raise the possibility of pyonephrosis, and an inadequately prepared endoscopic procedure can easily induce urosepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Yuruk et al [ 32 ] showed that the CT values of pus in pyonephrosis patients were significantly higher than those of patients with hydronephrosis; the difference was statistically significant. Because pus often contains infectious substances, cell debris, and large numbers of micro-organisms, the CT value of the pus is higher than hydronephrosis, and application of CT values based on CT thin-layer scanning to identify hydronephrosis and pyonephrosis yields satisfactory results [ 33 ]. In clinical practice, a significant increase in CT attenuation value of hydronephrosis should raise the possibility of pyonephrosis, and an inadequately prepared endoscopic procedure can easily induce urosepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical issues can be developed by urinary calculi, such as pyonephrosis, UTI with sepsis or renal deterioration (3,4). The persistence of upper urinary tract lithiasis can lead to hydronephrosis, which promotes local kidney complications such as total parenchyma destruction, including infections (5).…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria enters into the bloodstream as a consequence of acute renal empyema, leading to serious infectious disorders such sepsis that may harm the body functions [30].…”
Section: Discussionmentioning
confidence: 99%